Introduction to ORC–VCC Systems: A Review - Tomasz Suchocki (Energies)
The increasing demand for sustainable energy solutions has spurred significant interest in cogeneration technologies. This study introduces a novel integrated organic Rankine cycle (ORC) and vapor compression cycle (VCC) system, specifically designed to enhance energy efficiency and reduce greenhouse gas emissions in industrial applications and district heating systems. The key innovation lies in the development of an advanced coupling mechanism that seamlessly connects the ORC and VCC, enabling more efficient utilization of low-grade heat sources. By optimizing working fluid selection and implementing a shared shaft connection between the ORC turbine and VCC compressor, the system achieves dual functionality—simultaneous electricity generation and cooling—with higher efficiency than conventional methods. Thermodynamic analyses and experimental results demonstrate that the proposed ORC–VCC system can significantly reduce operational costs and decrease reliance on fossil fuels by leveraging renewable energy sources and industrial waste heat. Additionally, the study addresses integration challenges by introducing specialized components and a modular design approach that simplifies installation and maintenance. This innovative system not only enhances performance but also offers scalability for various industrial applications. By providing a detailed evaluation of the ORC–VCC integration and its practical implications, this work underscores the system’s potential to contribute substantially to a sustainable energy transition. The findings offer valuable insights for future research and development, highlighting pathways to overcome existing barriers in cogeneration technologies.